Antithrombin III levels in critically ill surgical patients: do they correlate with VTE? - Galinos Barmparas; Eric J Ley; Umar F Bhatti; Andrew Wang; Navpreet K Dhillon; Yassar M Hashim; Russell Mason (Trauma Surgery & Acute Care Open)
Objective Antithrombin III (ATIII) deficiency may result from hereditary or acquired reduction in ATIII levels and is associated with an increase in venous thromboembolism (VTE) in the general population. VTE is a potentially preventable complication in the critically ill surgical patients. The objective of this study was to evaluate the relation between ATIII levels and VTE in surgical intensive care unit (SICU) patients.Methods All patients admitted to the SICU from January 2017 to April 2018 who had ATIII levels drawn were included in the study. An ATIII level below 80% of normal was considered low. The rate of VTE during the same admission was compared among patients with normal and low levels of ATIII. Prolonged length of stay (LOS >10 days) and mortality were also measured.Results Of the 227 patients included, 59.9% were male. The median age was 60 years. Overall, 66.9% of patients had low ATIII levels. Trauma patients had a higher rate of normal ATIII levels, whereas those weighing more than 100 kg had a higher rate of low ATIII levels. Patients with low ATIII levels had higher VTE rates compared with those with normal ATIII levels (28.9% vs. 16%, p=0.04). Patients with low ATIII levels also had prolonged LOS (76.3% vs. 60%, p=0.01) and increased mortality (21.7% vs. 6.7%, p<0.01). Trauma patients with VTE were more likely to have normal ATIII levels (38.5% in low ATIII cohort vs. 61.5% VTE in normal ATIII cohort, p<0.01).Conclusion Critically ill surgical patients with low ATIII levels have higher incidence of VTE, longer LOS, and higher mortality. In contrast, critically ill trauma patients may have high incidence of VTE even with normal ATIII levels.Level of evidence III.